2023
DOI: 10.1002/jor.25640
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral joint geometry and osteoarthritis features 3–10 years after knee injury compared with uninjured knees

Abstract: In this cross‐sectional study, we compared patellofemoral geometry in individuals with a youth‐sport‐related intra‐articular knee injury to uninjured individuals, and the association between patellofemoral geometry and magnetic resonance imaging (MRI)‐defined osteoarthritis (OA) features. In the Youth Prevention of Early OA (PrE‐OA) cohort, we assessed 10 patellofemoral geometry measures in individuals 3–10 years following injury compared with uninjured individuals of similar age, sex, and sport, using mixed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although studies on the impact of trochlear morphology on knee pathologies often focus on extreme disorders leading to patellofemoral dislocation, it has been reported that extreme sulcus angles and shallow lateral trochlear inclination may predispose individuals to knee injuries. 24 Another study suggested that an increase in patellar tilt is associated with a higher risk of posterior cruciate ligament injury. 26 Whilst trochlear morphology has not consistently shown an association with knee pain in native knees, there is currently no study investigating how this relationship might manifest in individuals with haemophilia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies on the impact of trochlear morphology on knee pathologies often focus on extreme disorders leading to patellofemoral dislocation, it has been reported that extreme sulcus angles and shallow lateral trochlear inclination may predispose individuals to knee injuries. 24 Another study suggested that an increase in patellar tilt is associated with a higher risk of posterior cruciate ligament injury. 26 Whilst trochlear morphology has not consistently shown an association with knee pain in native knees, there is currently no study investigating how this relationship might manifest in individuals with haemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to proportionally reveal the morphological differences occurring in the patellofemoral joint, ratios such as pML/SA, SD/LCL, MFC-LFC/LFL, mFL/LFL and ID/LCL were also calculated. [23][24][25] The study employed two distinct analytical approaches to examine the relationship between arthropathy severity and measured variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation